Design and Simulation of CMOS Based Potentiostat for Redox Sensor Application - Ooi , Sin Chein (2016)

(untitled)
Redox sensor is widely used to detect certain analytes of a chemical solution,for example concentration of a chemical solution. Redox sensor have advantages of detection of multiple ions inside a sensing areas and made measurement and represent it in electrical current or voltage. However when sensing areas is decrease due to miniaturization of sensor, sensor output signal is decrease as well, this is undesired outcome. This thesis will present a design of a potentiostat that able to process the redox sensor small output signal in the range of 0A to 10A and have a linear and amplified voltage signal at the output of the potentiostat for integration with ADC circuit. The potentiostat systems contain three functional blocks which made up of Sensor, Reference and Amplifier blocks. Sensor block is constructed to model the real redox sensor and must able to linearly copying current signal to the output. For reference blocks is to act as a constant current sources for two input terminal of the Amplifier blocks. Finally, the Amplifier blocks is designed to be a differential input and single-ended output amplifier which able to linearly convert and amplifier the redox sensor current signal to voltage. The designed amplifier able to achieve DC gain of 23.32dB, phase margin of 90.588º,common-mode gain of -76.019dB, slew rate of 244.43 V/μs, power supply rejection ratio of 29.414dB, and also common-mode rejection ratio of 99.329dB. The layout design for the full potentiostat systems is done with the die areas about 1719.876 and the potentiostat output voltage is range between 994.803mV and 1.47169V.